1999
DOI: 10.12968/denu.1999.26.3.94
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sources of Stress in Dental Students

Abstract: A 36-item questionnaire was used to investigate the stress perceived by students at Manchester Dental School to potential stressors, grouped under the headings of living accommodation, personal factors, educational environment, academic work and clinical factors. The stressors producing the highest ratings for perceived stress varied throughout the course but high values were allocated to examinations, fear of failing the course or year, shorter and fewer holidays than other university students and--for clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
134
4
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(165 citation statements)
references
References 0 publications
18
134
4
9
Order By: Relevance
“…This observation suggests that students may feel better about themselves when interacting with others, which supports the view that early engagement with patients is 'protective' in terms of stress and burnout. [19] The opposite, where engagement with 'self ' was reported at a higher frequency on EE and a lower frequency on PA, may indicate that students are challenged to cope in an academic environment. This finding may be consistent with the fact that a number of stressors noted in the DES were located in the 'self-efficacy beliefs' category.…”
Section: Response To the Mbimentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that students may feel better about themselves when interacting with others, which supports the view that early engagement with patients is 'protective' in terms of stress and burnout. [19] The opposite, where engagement with 'self ' was reported at a higher frequency on EE and a lower frequency on PA, may indicate that students are challenged to cope in an academic environment. This finding may be consistent with the fact that a number of stressors noted in the DES were located in the 'self-efficacy beliefs' category.…”
Section: Response To the Mbimentioning
confidence: 99%
“…Stress among students in various disciplines in the health sciences is well documented. [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, the literature on stressors among students and qualified dental hygienists is sparse. [7,14,[20][21][22] Sources of environmental stress among dental students have been identified and quantified by means of the Dental Environment Stress (DES) questionnaire.…”
mentioning
confidence: 99%
“…In relation to their concerns, the focus of students on course requirements and the related issue of insufficient experience of procedures is unsurprising in itself, given that Heath et al 9 identified 'completing clinical treatment requirements', as the most important source of stress for fourth year students. Although requirements were relevant to both the outreach and the dental hospital, the issue was not raised much in relation to the latter.…”
Section: Much Of the Equipment At The Clinic Is Faulty (1)mentioning
confidence: 99%
“…In the last year of the undergraduate program, emotional exhaustion becomes more evident and ends up predisposing the students to common mental disorder. 3,[6][7][8][9][10][11] We know from the literature that the prevalence of common mental disorder in industrialized countries ranges from 7 to 30%. 4 Similar studies drawn from the Brazilian population, showed that this prevalence varied from 22 to 35%.…”
Section: Introductionmentioning
confidence: 99%